Two Closely Linked Mutations in DROSOPHILA MELANOGASTER That Are Lethal to opposite Sexes and Interact with Daughterless - Cline, Thomas W. (1978)
A new spontaneous mutation named Sex-lethal, Male-specific #1 (Sxl(M1)) is described that is lethal to males, even in the presence of an Sxl(+) duplication. Females homozygous for Sxl(M1) are fully viable. This dominant, male-specific lethal mutation is on the X chromosome approximately 0.007 map units to the right of a previously isolated female-specific mutation, Female-lethal, here renamed Sex-lethal, Female-specific #1 (Sxl(F1)). Sxl(M1) and Sxl(F1) are opposite in nearly every respect, particularly with regard to their interaction with the maternal effect of the autosomal mutation, daughterless (da). Females that are homozygous for da produce defective eggs that cannot support female (XX) development. A single dose of Sxl(M1) enables daughters to survive this da female-specific lethal maternal effect. A duplication of the Sxl locus weakly mimics this action of Sxl(M1). In contrast, Sxl(F1) and a deficiency for Sxl, strongly enhance the female-lethal effects of da. The actions of Sxl(M1) and Sxl(F1) are explained by a model in which expression of the Sxl locus is essential for females, lethal for males, and under the control of a product of the da locus. It is suggested that Sxl(M1) is a constitutive mutation at the Sxl locus.